2019
DOI: 10.1039/c9ra04416g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data revealing explosion characteristics of methane, air, and coal mixtures

Abstract: The explosion characteristics of methane–air–coal dust mixtures were investigated using an XKWB-1 sealed explosion system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The above findings showed that the coupling of fine water mist containing 7% KCl and 20% CO 2 had a better suppression effect on the temperature of the explosion flame wave. 35,36 The qualitative conclusions obtained in this study are consistent with the relevant descriptions in refs11 39,and42. It demonstrates that the conclusions obtained in this paper can describe the effective method of suppressing methane explosion in the pipeline network and can also provide theoretical reference and support for suppressing the methane explosion event in the actual mine roadway network.…”
Section: Explosion Suppression Effect Of Coupling Water Mist With An ...supporting
confidence: 91%
See 2 more Smart Citations
“…The above findings showed that the coupling of fine water mist containing 7% KCl and 20% CO 2 had a better suppression effect on the temperature of the explosion flame wave. 35,36 The qualitative conclusions obtained in this study are consistent with the relevant descriptions in refs11 39,and42. It demonstrates that the conclusions obtained in this paper can describe the effective method of suppressing methane explosion in the pipeline network and can also provide theoretical reference and support for suppressing the methane explosion event in the actual mine roadway network.…”
Section: Explosion Suppression Effect Of Coupling Water Mist With An ...supporting
confidence: 91%
“…Under the working conditions of fine water mist containing 7% KCl and 20% CO 2 , the peak flame temperatures in branch pipes 1 to 5 decreased by 82.4, 82.3, 82.2, 82.3, and 82.2%, respectively, compared to without explosion suppression measures. The above findings showed that the coupling of fine water mist containing 7% KCl and 20% CO 2 had a better suppression effect on the temperature of the explosion flame wave. , …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Researchers discovered that the explosion of hybrid mixtures occurs when both dust and gas concentrations are lower than the minimum explosion concentration of the single substances [8][9][10]. Deng et al [11] conducted methane-air-coal dust explosion in an XKWB-1 sealed explosion system. They found that when 500 g/m 3 coal dust and methane explode, the maximum explosion pressure is linearly related to methane concentration and volatile content of coal dust, decreased with an increase in methane concentration, and increased with volatile content of coal dust.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is an important energy source and chemical raw materials [1][2][3][4]. Many disasters may occur in the process of coal mining [5][6][7][8][9][10][11]. As one of the main disasters, coal spontaneous combustion (CSC) not only burns vast coal resources and releases toxic gases but also causes casualties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%